(untitled) (Bangladesh Journal of Medical Science, 2014)
It is supposed that the most frequent birth defect worldwide is clefts of the lip and/or palate (CL+-P). The frequency is non-syndromic where CL+-P happens in segregation of additional phenotypes; and syndromic clefts are referred when one or more additional features are involved. The etiologies of CL+-P is multifaceted and occupy both major and minor genetic influences with changeable relations from environmental factors. This study extends the involvement of various genes, which are responsible for both syndromic and non syndromic CL+-P patients. DOI: http://dx.doi.org/10.3329/bjms.v14i1.20928 Bangladesh Journal of Medical Science Vol.14(1) 2015 p.113-116